Test of Acceptability and Fe Levels Pancake “Bilor” Beetroot and Moringa Leaves as a Snack to Prevent Anemia in Adolescent Girls - Sisca Indah Mentari; Ani Intiyati; Nuning Marina Pengge; Mujayanto Mujayanto (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Iron deficiency anemia is a major health problem that occurs in adolescent girls. Prevention of anemia in adolescent girls is carried out with food innovations that are high in iron. This study aims were to determine the acceptability and content of Fe in beetroot and moringa “BILOR” pancakes as a snack to prevent anemia in adolescent girls. This type of research uses experimental research with a complete random design. There are three formulations with the addition of wheat flour:beet flour:moringa leaves flour, PB1 (85:0:0), PB2 (50:20:15), PB3 (50:25:10). A total of 2,700 grams of samples for 30 panelists were organoleptically tested using a hedonic scale and analyzed with the Kruskal Wallis test and the Mann Whitney test. Based on the results of the acceptability test on the PB1 control formulation was preferred by the panelists, while the PB3 treatment formulation with an iron content of 6.88mg was considered the best and qualified as a snack. It is hoped that the formulation of the “BILOR” pancake can be improved and developed again for better results.